The Management Accounting Usage in Automotive Servitized Companies: An Initial Attempt - Unggul Purwohedi; Muhammad Kaleem Zahir-ul-Hassan; Maqsood Memon (Universitas Negeri Semarang, 2023)
Purpose : Prior literature suggests a further exploration on the usage of management accounting (MA) techniques in the servitization context. Servitization is a movement in which companies consciously develop service offerings, which support their products to gain competitive advantage. There are still limited studies of this topic in the context of Indonesian manufacturing companies, thus this paper aims to provide evidence on the usage of MA in servitized manufacturing companies in Indonesia. Method : We employed a qualitative approach as well as a preliminary survey to a number of selected managers and accountants from four different automotive companies. Findings : The result shows that target costing is very crucial to the automotive manufacturing companies nowadays. We discover that competitive position monitoring, quality costing, integrated performance measurement, and brand management accounting are relevant to company’s strategic position. Therefore, we find the connection between the usage of MA and company’s strategic planning. Novelty : From practical point-of-view, our study provides the evidence on the usage of MA in Indonesian servitized-manufacturing business. Also, we build a framework, which represents the relationship between the MA techniques and servitization, that could benefit business through a better understanding about the interconnections between MA usage and servitization level. Keywords : Management Accounting; Servitization; Automotive Companies; Indonesia